Colaboradores - Geraldello, Camilla Silva (Faculdade de Filosofia e Ciências, 2016)
Alexandre César Cunha Leite Angélica Saraiva Szucko Clodoaldo Bueno Damian Popolo Gary Rainer Chumacero Vanderlei Gisele BellinatiGraziene Carneiro de SouzaJulieta Zelicovich Marcos Alan S. V. Ferreira Marketa Maria Jerabek  Thamirys Ferreira Cavalcante